DISIPLIN KERJA KARYAWAN HOUSEKEEPING DI HOTEL KOH TIEN MENG (KTM) RESORT BATAM - Maulina "; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is about work discipline of housekeeping employee at Hotel KTM Resort Batam. This study aims to (1) be able to know the existing rules in housekeeping department at Hotel KTM Resort Batam. (2) can know the working discipline of hosekeeping department employees at KTM Resort Batam Hotel. The sample in this study amounted to 14 people using census sempling technique. This research uses quantitative descriptive to categorize data and then use interview. And for data collection techniques in this study using observation and interviews. Based on the results obtained on the motivation of employee housekeeping work at Koh Tien Meng (KTM) Resort Batam is quite good. This is evidenced by interviews in accordance with predetermined indicators.Keywords: Discipline, Housekeeping